1991
DOI: 10.1021/bi00104a001
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic characterization of phospholipase A2 modified by manoalogue

Abstract: Manoalogue, a synthetic analogue of the sea sponge-derived manoalide, has been previously shown to partially inactivate the phospholipase A2 from cobra venom (Reynolds, L. J., Morgan, B. P., Hite, E. D., Mihelich, E. D., & Dennis, E. A. (1988) J. Am. Chem. Soc. 110, 5172) by reacting with enzyme lysine residues. In the present study, the inactivation of the phospholipases A2 from pig pancreas, bee venom, and cobra (Naja naja naja) venom by manoalogue was studied in detail. Manoalogue-treated enzymes were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Thus, it can now be concluded that the major attachment site is responsible for inactivation. The presence of enzyme-bound manoalide may prevent the region of the i-face near K94 from tightly interacting with the interface, although manoalide modification does not prevent interfacial binding, and it leaves the active site functional for the hydrolysis of short-chain phospholipids (32). Also, interfacial binding of manoalogue-modified bvPLA2 does not result in complete desolvation of the microenvironment between the interface and the enzyme (32).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can now be concluded that the major attachment site is responsible for inactivation. The presence of enzyme-bound manoalide may prevent the region of the i-face near K94 from tightly interacting with the interface, although manoalide modification does not prevent interfacial binding, and it leaves the active site functional for the hydrolysis of short-chain phospholipids (32). Also, interfacial binding of manoalogue-modified bvPLA2 does not result in complete desolvation of the microenvironment between the interface and the enzyme (32).…”
Section: Discussionmentioning
confidence: 99%
“…Mutant proteins were stored at ÏȘ80°C. The protein concentrations of recombinant bvPLA 2 solutions were obtained from the absorbance at 280 nm (38) and by the Bradford assay (Bio-Rad) using commercial bvPLA 2 (Boehringer Mannheim) as a standard (both methods gave similar results). The enzymatic activities of the mutants were assayed using a spectrofluorimeter (Jasco 821-FP) with the fluorescent substrate 1-palmitoyl-2[10-(1-pyrene)decanoyl]-sn-glycerol-3-phosphomethanol lithium salt (39).…”
Section: Methodsmentioning
confidence: 99%
“…Mechanistic studies show that these compounds covalently modify multiple lysine residues found on the surface of many different sPLA2s. In the case of one detailed study, it was shown that manoalogue, a structural analog of manoalide, forms more than 20 distinct molecular adducts with bee venom sPLA2 (41). Thus, it is highly likely that these compounds inactivate several different classes of enzymes in cells.…”
Section: Spla2 Inhibitorsmentioning
confidence: 99%